The Effect of Profitability, Liquidity and Company Size on Disclosure of Financial Statements on The Jakarta Islamic Index - BillY Dewantara; Fernando Africano; Lidia Desiana; Rini Rini (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This research was conducted to find out how the influence of profitability, liquidity, and company size on the disclosure of financial statements in manufacturing companies listed on the Jakarta Islamic Index (JII) for the 2016-2021 period. This study uses a quantitative approach with secondary data sources. Samples were selected using purposive sampling that met the criteria selected in determining the sample were 10 companies, according to the characteristics of the study. The data used is annual financial report data from 2016-2021. The method used is descriptive analysis, classical assumption test, multiple linear regression test and hypothesis testing using the E-Views Version 12 computer program. The results of this study indicate that partially (individually) the profitability variable has a positive and significant effect on the disclosure of financial statements. Liquidity has a negative and significant effect on the disclosure of financial statements for manufacturing companies listed. Company size has a negative and significant effect on financial statement disclosure for manufacturing companies listed. Simultaneously (together) profitability, liquidity, and company size have a significant effect on the disclosure of financial reports for manufacturing companies listed. It can be concluded that only the profitability variable has a positive and significant effect on financial statement disclosure in manufacturing companies.